1997
DOI: 10.1007/s004240050427
|View full text |Cite
|
Sign up to set email alerts
|

K V LQT channels are inhibited by the K + channel blocker 293B

Abstract: Previous data have indicated that the chromanol 293B blocks a cAMP activated K+ conductance in the colonic crypt, a K+ conductance in pig cardiac myocytes and the K+ conductance induced by IsK protein expression in Xenopus oocytes. We have also shown that cAMP-activated cystic fibrosis transmembrane conductance regulator (CFTR) up-regulates, apart from the typical Cl- current, a 293B- inhibitable K+ current. Very recently it has been shown that the IsK protein interacts with KVLQT subunits to produce a K+ chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 0 publications
3
46
0
Order By: Relevance
“…Exposure at stage 41 to Chromanol 293B, a specific blocker of KCNQ1 (27), also resulted in hyperpigmentation (Fig. S3), consistent with inhibition of KCNQ1 being responsible for hyperpigmentation.…”
Section: Kcne1 Misexpression Depolarizes Embryonic Cells By Inhibitiosupporting
confidence: 56%
“…Exposure at stage 41 to Chromanol 293B, a specific blocker of KCNQ1 (27), also resulted in hyperpigmentation (Fig. S3), consistent with inhibition of KCNQ1 being responsible for hyperpigmentation.…”
Section: Kcne1 Misexpression Depolarizes Embryonic Cells By Inhibitiosupporting
confidence: 56%
“…In our previous experiments utilizing forskolin and IBMX [16] all the resident Cl -channels might have been activated maximally. This hypothesis would agree with a previous study [35] in which we showed that the effects of neurotensin and ATP in HT 29 could be potentiated by cAMP. The present studies would also be in agreement with other hypotheses of CFTR regulation of other as yet unidentified pathways.…”
Section: Discussionsupporting
confidence: 80%
“…This latter conclusion may not be correct because CHO cells possess small endogenous Cl -channels [28] and because CFTR can also generate a variety of indirect effects. These can be summarized as follows: interference with membrane trafficking [13][14][15], inhibition of epithelial Na + channels (ENaC) [4,6,7]; modulation of Kir1.1 (ROMK1) K + channels [9]; interaction with I Ks (K v LQT 1 and minK) [8,29], and modulation of water transport [11].…”
Section: Discussionmentioning
confidence: 99%
“…We therefore investigated the possible implication of K cAMP channels in the UDP-mediated I sc stimulation. In IL-13-treated NHBE cells, chromanol 293B (100 µM), a specific inhibitor of the KCNQ1 channel, part of the K cAMP channel [12,[48][49][50] did not affect the amplitude of the two UDPstimulated I sc components (I fast was of 24.8 ± 2.9 µA.cm in absence or presence of chromanol respectively, n=6). Chromanol effect on basolateral 86 Rb effluxes was also investigated upon UDP application.…”
Section: Are Apical K Channels Involved In Udp and Ionomycin-stimulatmentioning
confidence: 99%